PENGEMBANGAN TES FORMATIF INTERAKTIF PPKN BERBASIS WEB UNTUK PEMBELAJARAN DI SD NEGERI 60/VI PAYO LEBAR - Arifin, Akhmad; Yamin, Martinis; Putra, Darma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Formative assessment plays a crucial role in monitoring students’ learning progress; however, its implementation in elementary schools remains suboptimal due to limited instructional time, the dominance of manual assessment practices, and delayed feedback for students. This study aimed to develop a web-based interactive formative assessment for Civic Education (PPKn) and to examine its validity, practicality, and effectiveness in improving students’ learning outcomes at SD Negeri 60/VII Payo Lebar. The study employed a Research and Development (R&D) approach using a modified Tessmer model, consisting of the stages of preliminary analysis, self-evaluation, prototyping (expert review, one-to-one, and small group), and field testing. The participants were 25 fifth-grade students. Data were collected through expert validation sheets, student and teacher response questionnaires, and learning achievement tests. The results indicated that the developed product, Seloko Edu, met the criteria of high validity based on material and media expert evaluations. Student responses in the one-to-one and small group trials showed that the assessment was practical and engaging, while field test results revealed that the system was easy to use and facilitated students’ understanding of the learning material. Furthermore, learning outcome analysis showed that 88% of students achieved the minimum mastery criterion (KKM ≥ 70), indicating an improvement in cognitive achievement after using the web-based formative assessment. Therefore, the Seloko Edu interactive web-based formative test is considered valid, practical, and effective as a formative evaluation tool in elementary Civic Education learning.